Polymorphism of XRCC1 Gene Exon 6 (Arg194Trp) in Relation to Micronucleus Frequencies in Hospital Radiation Workers - H. N.E. Surniyantoro; Y. Lusiyanti; T. Rahardjo; D. Tetriana; S. Nurhayati; H. Date (Atom Indonesia, 2018)
The genetic polymorphism of DNA repair gene plays some important role in regulating individual sensitivity to ionizing radiation, maintaining DNA integrity, and preventing cancer and DNA damage.XRCC1 as one of the members ofbase excision repair (BER) is involved in the repairement of oxidized bases and single-strand breaks DNA after exposure by ROS, including ionizing radiation. This study was aimed to examine the correlation between XRCC1 exon 6 gene polymorphism and MN frequency in radiation workers and their relation to age, gender, smoking status and years of exposure. This study involved 81 hospital radiation workers and 20 controls from several hospitals in Indonesia. Genotyping of XRCC1exon 6 gene polymorphism and MN assay were performed using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and Cytokinesis-Block Micronucleus assay (CBMN assay), respectively.  The results indicated that MN frequency was significantly higherin the exposed workers than in the controls (15.38±7.72 versus 9±5.49; p = 0.001).Radiation workers with heterozygous alleles for XRCC1 polymorphisms showed a significantly higher MN frequency than controls with the same genotypes (17.5±8.36 versus 7.44±5.05; p = 0.002). The confounding factors, like gender and age, were significantly associated with increased MN frequency both in radiation workers and controls. Smoking status was significantly associated with MN frequency in the controls only, while years of exposure did not affect MN frequency either in radiation workers or controls. These results suggest that the genetic polymorphism of XRCC1 gene exon 6 with a mutant heterozygous/ CT variant demonstrated an association with the extent of DNA damage in the hospital radiation workers in this study. In the subsequent studies, it is necessary to examine the DNA repair genes polymorphism in populations with controlled non-genetic factors, such as lifestyles, environments, and exercises that affect the MN frequency as a biomarker of DNA damage.